The long kiss goodnight [videorecording (DVD)] - Harlin, Renny; Davis, Geena; Jackson, Samuel L.; Malahide, Patrick; Bierko, Craig; Cox, Brian, 1946-; Morse, David, 1953-; Spradlin, G. D. (New Line Home Video, 2000)
A schoolteacher learns that she was once a lethal assassin for the CIA, and teams up with a wise-cracking detective to uncover her past before a hi-tech army of corrupt government renegades kills them both.